DERECHO FUNDAMENTAL A LA VIVIENDA Y POLÍTICAS PÚBLICAS EN COLOMBIA (2019)
The present text shows in a critical and reflective way the development of the right to housing in Colombia from a legal-administrative perspective, reviewing the general principles of the right to housing in the national and international framework, identifying the contents of the fundamental right at stake and unifying the mandates that derive from it, to be able to verify the coherence of the general policies regarding these guarantees.